2019
DOI: 10.26501/jibm/2019.0901-005
|View full text |Cite
|
Sign up to set email alerts
|

Re-visiting Current Debate on Shar¯ı‘ah Position of Derivatives

Abstract: The current practices in Money, Capital, Foreign Exchange and Securities markets, based on interest and short selling, stress upon using hedging instruments for risk management. Nevertheless, there is disagreement among scholars and researchers regarding permissibility status of these instruments. Although majority of Islamic economists and scholars have expressed serious concern on the use of financial engineering products, a number of scholars insist on their use by the Islamic financial institutions. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…Literature explored inevitability of market risk, and the Islamic banks need to reduce this exposure to price and rate volatility for by hedging instruments. The primary benefit of hedging is that it minimizes the risk of investment significantly (Anwer & Habib, 2019; Froot, Scharfstein, & Stein, 1993). Ayoub (2013) suggested that Islamic banking and finance industry can improve their growth by using hedging strategy, from this way Islamic finance industry share will increase due to stable and competitive pricing of a product of Islamic banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature explored inevitability of market risk, and the Islamic banks need to reduce this exposure to price and rate volatility for by hedging instruments. The primary benefit of hedging is that it minimizes the risk of investment significantly (Anwer & Habib, 2019; Froot, Scharfstein, & Stein, 1993). Ayoub (2013) suggested that Islamic banking and finance industry can improve their growth by using hedging strategy, from this way Islamic finance industry share will increase due to stable and competitive pricing of a product of Islamic banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…H .ā jah can be employed only if there is no opposite explicit text, while there is a certain text (Sunnah) against it. Therefore, wa'dān based Islamic foreign exchange forward contracts should not be granted the license of permissibility using the h .ā jah maxim, particularly, because the IFIs have started using the same for investing in financial derivatives without the need for hedging and without fulfilling the conditions of underlying contracts (Anwer & Habib, 2019).…”
Section: Misuse Of H ā Jah Maxim In Islamic Banking and Financementioning
confidence: 99%
“…Meskipun hasilnya tidak definitif, mereka memberikan argumen untuk adopsi pembagian risiko, sebagai lawan dari transfer risiko (Kok et al, 2014). Anwer (2019) dalam penelitiannya mengevaluasi status kebolehan derivatif berdasarkan fitur utama hukum kontrak dalam Islam. Hasil penelitiannya menunjukan bahwa instrumen derivatif lindung nilai satu sisi dapat membawa berbagai keuntungan bagi institusi namun penggunaan derivatif menyebab kan kerapuhan dalam sistem keuangan global dan pasar karena keterlibatan gharar, short selling dan bunga.…”
unclassified
“…Struktur derivatif ini sangat rumit yang mengarah pada penyimpangan dari aktivitas ekonomi nyata sehingga sulit juga untuk menghindari larangan Syariah. Negaranegara dan cendekiawan Muslim perlu mengembangkan instrumen-instrumen khusus untuk melindungi risiko dengan cara yang sesuai dengan Syariah (Anwer & Habib, 2019). Uddin (2020) (Chance & Brooks, 2015).…”
unclassified
See 1 more Smart Citation